Implementasi Token-Based Access Control dan Proteksi Konten pada Manajemen Pembelajaran Berbasis Web untuk Meningkatkan Keamanan Data di Institusi Pendidikan Medis - Ahmad Sulaeman; Joko Aryanto (JSAI (Journal Scientific and Applied Informatics), 2025)
Digital content security is a critical aspect in the implementation of online learning systems, especially in medical education institutions that manage sensitive video data. This study aims to develop and evaluate a web-based video content protection system by integrating three main methods: AES-128 encryption, Token-Based Access Control, and Dynamic Watermarking. The AES-128 encryption method is applied to secure video files so that only authorized users can decrypt and access them, while Token-Based Access Control serves as a dynamic session-based authentication mechanism to prevent unauthorized access. In addition, Dynamic Watermarking embeds user identity information into each video playback to trace and deter illegal content distribution. Experimental results show a Token Validation Success Rate of 100% and an Intrusion Detection Rate of 90%, indicating that the system performs well in verifying authentication and detecting unauthorized access. Performance testing of the HTTP Live Streaming (HLS) process achieved an average response time of 1.79 seconds with 1000 successful requests and no failures, demonstrating that the additional security layers did not significantly degrade system performance. Overall, this study concludes that the integration of AES-128 encryption, Token-Based Access Control, and Dynamic Watermarking provides an effective multilayer security approach for protecting video-based learning content and strengthening data security in medical education environments.